2020
DOI: 10.1002/csc2.20169
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of nitrogen fertilizer management for improving rice grain yield and nutrient accumulation and mobilization in saline‐alkaline soils

Abstract: Soil salinity and alkalinity are key abiotic stresses that limit crop growth and yield worldwide. Balanced N fertilization is important for improving rice (Oryza sativa L.) yield via efficient utilization of P and K under saline and alkaline soil conditions. In this study, a japonica rice cultivar, Kenjing 8, was used to investigate the effects of N fertilizer on rice yield, as well as N, P, and K status, in a 2‐yr field experiment in saline‐alkaline soil in Heilongjiang Province, northeast China. The plants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Among yield components, panicle and spikelet number was the basis of stable high yield of rice (Sheehy et al, 2001;Yan et al, 2010;Guo et al, 2020;Li et al, 2021). Our results showed that the number of panicles per hectare and spikelets per panicle were significantly increased with increasing grain yield levels (Table 2).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Among yield components, panicle and spikelet number was the basis of stable high yield of rice (Sheehy et al, 2001;Yan et al, 2010;Guo et al, 2020;Li et al, 2021). Our results showed that the number of panicles per hectare and spikelets per panicle were significantly increased with increasing grain yield levels (Table 2).…”
Section: Discussionmentioning
confidence: 64%
“…Frontiers in Environmental Science frontiersin.org documented in several previous studies (Rose et al, 2010;Bi et al, 2013;Wang et al, 2017;Wei et al, 2017;Guo et al, 2020). 60-90% of P taken up by the rice is typically accumulated in the grains at maturity (Rose et al, 2010;Bi et al, 2013).…”
Section: Yield Level (Mg Hamentioning
confidence: 92%
See 3 more Smart Citations